Understanding the lived-experience and support-needs of people living with antimicrobial resistance in the UK through interpretative phenomenological analysis - Ryan A. Hamilton; Benjamin Lond; Lucina Wilde; Iain Williamson (Scientific Reports, 2024)
Abstract In the UK nearly 54,000 infections were caused by serious resistant bacteria in 2022 but there is a lack of evidence regarding the long-term impact on patients’ lives nor what support they need. This research aimed to answer the question: “What are the key elements of experience and support needs of people living with AMR in the UK?”. In-depth semi-structured interviews were undertaken with nine people who had been living with resistant infections or colonisation for 12-months or longer. Interpretive Phenomenological Analysis was used to study the accounts and illustrate individuals’ experiences and support-needs. Participants experienced marginalisation and isolation but also empowerment; described across three major themes: (1) I live in fear and stigma: The long-term impact of AMR; (2) I am battling on my own: A journey toward self-advocacy; and (3) I like to share my story: The role of AMR communities. All participants perceived a lack of knowledge, information, and support from clinicians; difficulties accessing reliable and understandable information; and lack of understanding from family and friends. Charities and online groups provided support with coping with their situation and improving mental health and wellbeing. Understandable and relatable information regarding the science of AMR, transmission, prevention, and living with AMR needs to be provided by clinicians and healthcare services around the time of diagnosis to readily available after diagnosis.